First-principles calculations of the magnetocrystalline anisotropy of the prototype 2:17 cell boundary phase Y(Co1-x-yFexCuy)5 - Patrick, CE; Matsumoto, M; Staunton, JB (Elsevier, 2019)
We present a computational study of the compound YCo 1-x-y Fe x Cu y5 for 0 ⩽x,y⩽0.2. This compound was chosen as a prototype for investigating the cell boundary phase believed to play a key role in establishing the high coercivity of commercial Sm-Co 2:17 magnets. Using density-functional theory, we have calculated the magnetization and magnetocrystalline anisotropy at zero temperature for a range of compositions, modeling the doped compounds within the coherent potential approximation. We have also performed finite temperature calculations for YCo 5 , YCo 0.838 Cu 0.1625 and YCo 0.838 Fe 0.081 Cu 0.0815 within the disordered local moment picture. Our calculations find that substituting Co with small amounts of either Fe or Cu boosts the magnetocrystalline anisotropy K, but the change in K depends strongly on the location of the dopants. Furthermore, the calculations do not show a particularly large difference between the magnetic properties of Cu-rich YCo 0.838 Cu 0.1625 and equal Fe-Cu YCo 0.838 Fe 0.081 Cu 0.0815 , despite these two compositions showing different coercivity behavior when found in the cell boundary phase of 2:17 magnets. Our study lays the groundwork for studying the rare earth contribution to the anisotropy ofSmCo 1-x-y Fe x Cu y5 , and also shows how a small amount of transition metal substitution can boost the anisotropy field of YCo 5 .